(untitled) (SCIENCE TIME JOURNAL, 2025)
Phonetics, the branch of linguistics concerned with the physical properties of speech sounds, plays a vital role in understanding human communication. This article provides an overview of the three main subfields of phonetics: articulatory, acoustic, and auditory phonetics. It discusses the significance of phonetics in language learning, speech therapy, and technology, highlighting its applications across various domains. By examining the fundamental principles of phonetics, this article aims to enhance appreciation for the complexity of speech sounds and their role in effective communication.